Trustworthiness and Trust as Drivers of Value Perception and Its Implications for Positive Word of Mouth Intention (Study on the Context of Private Campuses in Jabodetabek) - Lovita Fillyand; Whony Rofianto (Indonesia Banking School, 2020)
This research to understand for trustworthiness and trust in implication for perception value of implemen-tation for positive word of mouth intention. Study from private universities in Jabodetabek. Object research this is a student of private universities those who live in jabodetabek. To answer problems in this research and the testing of hypotheses research, data analysis using Structural Equation Model (sem) - amos to know how strong the influence of every variable the treatment, this study found that the variable to connect for trust, perceived value and student loyalty have dimension operational competence, operational benevo-lence, and problem solving orientation as benchmarks of Trust in the institution personnel and Trust in the institutions management to create Perceived Value to the campus and generate student loyalty is expected to be able to have a positive influence on increasing student trust.